Closing the gap in care of blunt solid organ injury in children. Issue 5 (November 2020) - Yung, Nicholas; Solomon, Daniel; Schuster, Kevin; Christison-Lagay, Emily
Abstract : INTRODUCTION: Cross-sectional data of pediatric blunt solid organ injury demonstrates higher rates of nonoperative management and shorter lengths of stay (LOSs) in pediatric trauma centers (PTCs) versus adult trauma centers (ATCs) or dual trauma centers (DTCs). Recent iterations of guidelines (McVay 2008, J Pediatr Surg 2008;43(6):1072-1076 J Trauma Acute Care Surg 2015;79(4):683–693) have emphasized physiologic parameters rather than injury grade in clinical decision making, improving resource allocation and decreasing LOS. We sought to evaluate how these guidelines have influenced care. METHODS: The National Trauma Data Bank (2007–2016) was queried for isolated spleen and liver injuries in patients younger than 19 years. Linear regression, odds ratio (OR), and χ 2 test were used to determine significance between operative intervention or LOS among different trauma center types and grade of injury. RESULT: A total of 55, 036 blunt spleen or liver injuries were identified. Although operative rates decreased in ATCs over time ( p = 0.037), patients treated at ATCs or DTCs continued to demonstrate higher ORs of operative intervention (OR, 4.43 and 2.88, respectively) compared with PTCs. Mean LOS decreased by 1.52 ( p < 0.001), 0.49 ( p = 0.26), and 1.31 ( p = 0.05) days at ATC, DTC, and PTC to 6.43, 6.68, and 5.16 days. Improvement in LOS for ATCs was distributed across injury Grades I, II, and IV, while there was no correlation among PTCs for injury grade. CONCLUSION: Despite more than a decade of guidelines in pediatric solid organ injury supporting nonoperative management and accelerated discharge pathways based on physiologic parameters, rates of operative intervention remain much higher in ATCs versus PTCs, and all centers appear to fall short of consensus guidelines for discharge. LEVEL OF EVIDENCE: Care management study, level IV.